Community-based agricultural revitalization in Ngringo Village, Jaten Subdistrict, Karanganyar Regency - Nur, Aditya Ramadan; Pawitasari, Anisa; Maulida, Ara Shaula; Hapsoro, Hammam Rasendriya; Aprilia, Yohana Brenda; Antriyandarti, Ernoiz; Rahmianti, Nafisah (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Development involves conscious efforts and activities aimed at achieving positive change within a community. It requires the participation of all societal layers, with the government acting as a facilitator and guide. The government and the community must work harmoniously to achieve the desired goals. National agricultural development often focuses on villages close to municipalities, benefiting from hierarchical governance and advanced rural agricultural practices. This development can progress with political support, as outlined in Law Number 6 of 2014 on Villages, which aims to improve welfare, enhance human resources, and reduce rural poverty through sustainable management of local resources and the environment. This study aims to understand the potential and issues facing Ngringo Village, analyze the structural transformations, examine the institutional changes, assess the technology transfer, and identify a suitable agricultural development model. Methods: The research employs qualitative methods, including field observations, interviews with key informants, and analysis of secondary data from relevant literature and official documents. Findings: The results indicate that Ngringo Village has significant potential due to its strategic location and developed infrastructure. However, challenges such as reduced agricultural land and a shift in economic activities from agriculture to industrial sectors are evident. Institutional support through local farmer groups and technology adoption has been crucial in addressing some of these challenges. Conclusion: In conclusion, while Ngringo Village faces challenges due to rapid structural changes and urbanization, the village has managed to sustain its agricultural practices through effective institutional support and technology transfer. The study suggests that a location-based development model, considering both agricultural and non-agricultural factors, is essential for the sustainable development of Ngringo Village. Novelty/Originality of this study: This study produces a location-based agricultural development model that considers both agricultural and non-agricultural factors, providing practical guidance for local governments in planning sustainable development in villages facing rapid urbanization, such as Ngringo Village.